Prevalence of medical comorbidity in early onset versus late-onset depression in Vindhya region - Rajesh Singh (Wolters Kluwer Medknow Publications, 2021)
Background: Late-onset depression differs significantly from early-onset depression according to clinical features, physical comorbidities, cognitive impairment, and cerebrovascular abnormalities, which suggest that these might have differing etiopathological pathways toward the depressive phenotype. Aim: The aim of the study was to identify comorbid physical disorders with late-onset depression. Methods: The present cross-sectional study was conducted in inpatients of the Department of Psychiatry during a period of 18 months. A study consisted of 60 patients of first depressive episode diagnosed using International Classification of Diseases-10 criteria, segregated 2 different groups of Early onset depression (between 40 and 65 years) and late-onset depression (LOD) (>65 years) with 30 patients each. Results: In LOD group, predominant comorbidities were hypertension 56.6%, cerebrovascular disease 36.6%, diabetes 33.3%, cardiovascular disease 23.3%, and anaemia 23.3%, followed by respiratory illnesses, arthritis, benign prostatic hyperplasia and cirrhosis. While, in early-onset depression group, common comorbidities were hypertension (13.3%), anemia (10%), arthritis (10%), and diabetes (6.6%). Conclusions: Hypertension cerebrovascular disease, diabetes, and cardiovascular disease were the predominant comorbidities in late-onset as well as early onset depression.